Peran Guru dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X di MAN 2 Jombang - Fitriatul Azizah; Larasati Widoningtyas (Politeknik Kampar, 2025)
This research is motivated by the low interest of students in learning Economics in Class X at MAN 2 Jombang. One of the causes is that the teaching methods used by teachers are still lacking in variety and do not align with the characteristics of the students. However, teachers play a crucial role in creating an engaging learning environment, motivating students, and delivering material in a contextual manner. The research questions of this study are: (1) How do Economics teachers play a role in enhancing students' interest in learning Economics in Class X at MAN 2 Jombang? (2) What are the supporting and inhibiting factors for Economics teachers in enhancing students' interest in learning Economics in Class X at MAN 2 Jombang? The objectives of this research are: (1) To determine how teachers play a role in enhancing students' interest in learning Economics in Class X at MAN 2 Jombang. (2) To identify the supporting and inhibiting factors for teachers in enhancing students' interest in learning Economics in Class X at MAN 2 Jombang. This study employs a qualitative method. The research was conducted at MAN 2 Jombang with the subjects being Economics teachers and Class X students. Data collection techniques include observation, in-depth interviews, and documentation. The researcher plays a direct role as the main instrument in data collection. Primary data sources are obtained from direct interactions with teachers and students, while secondary data is obtained from supporting documents. The results of the study indicate that the role of teachers is very important in enhancing students' interest in learning Economics in Class X at MAN 2 Jombang. Teachers act as motivators, facilitators, and guides in the learning process. They use various innovative teaching methods, provide individual attention to students, and build good communication with them. Additionally, teachers strive to understand the characteristics and needs of students, enabling them to provide appropriate learning services.